PENGARUH MODEL PEMBELAJARAN PROBLEM SOLVING LEARNING DAN PROJECT BASED LEARNING TERHADAP HASIL BELAJAR SEJARAH DITINJAU DARI KREATIVITAS SISWA DI SMA NEGERI SE-SURAKARTA - Tamba, Evan Edo Asido; Mulyoto, M.; Sudiyanto, S. (HISTORIKA, 2019)
This research aims to find out: (1) Problem Solving Learning and Project Based Learning of Learning Out Comeshistory, (2) The difference effect between students who have high Creativity, medium and low creativity of learning out comes history, (3) the interaction effect between the uses of learning model with creativity in learning out comes history.This research is quantitative research with experimental method. The populations in this study are all students of SMA Negeriall-Surakartain 2015/2016 Academic Year. Sampling was done by cluster random sampling technique. The research sample are 68 students, they are: 35 students of experiment class Problem Solving Learning of experimental class SMA Negeri 1 Surakarta, 33 students ofcontrolÂ  classProject Based LearningSMA Negeri 3. The instrument uses to collect the data are questionnaires creativity and learning out-comes history test. The test instrument tryout involves content validity, difficulty level, differentiating power, and reliability. The tryout of interest questionnaires instrument involved content validity, internal consistency and reliability. Prerequisite includes tests of normality and homogeneity. The Hypothesis test is use two-way analysis of variance 2x3 with different cells.The results of the research show that: (1) There is differences between the effects of the use of learning modelProblem Solving Learning(PSL and Project Based Learning (PBL) on the learning out-comes history. This is evidenced by Fcount> F table (14.116> 5,66) at the 5% significance level. (2)The difference effect between students who have high interest and low interest of learning achievement history. This is evidenced by Fcount>Ftable (3.838> 5,66) at the 5% significance level. (3) There is no significant interaction between the learning model and interest in learning achievement of history. This is evidenced by Fcount<Ftable (1.076< 5,66) at the 5% significance level.